2220. Wirelessly Observed Therapy with a Digital Medicines Program to Optimize Adherence and Target Interventions for Oral Hepatitis C Treatment. (26th November 2018) - Bonacini, Maurizio; Kim, Yoona; Pitney, Caroline; McKoin, Lee; Tran, Melody; Landis, Charles
Abstract: Background: Real-world data on adherence to new oral hepatitis C virus (HCV) therapies are limited. Suboptimal adherence can lead to unnecessary treatment failures. Usual methods to measure adherence are inaccurate, and do not allow for opportune intervention. The digital medicines program (DMP) consists of DigiMeds™ (medicines with an ingestible sensor), a wearable sensor patch that confirms ingestion, the Proteus Discover ® mobile app, and secure web portal to allow for timely assessment of adherence, prevent missed doses, and maximize the likelihood of sustained virologic response (SVR), or cure. This study evaluated adherence and virologic outcomes in chronic HCV patients treated with sofosbuvir/ledipasvir (SOF/LDV) using the DMP. Methods: This was a single-arm, prospective, open-label, pilot study at two sites. SOF/LDV tablets co-encapsulated with ingestible sensors allowed the DMP to record ingestion adherence rates (number of ingestions detected/number of expected ingestions). Other outcomes were medical interventions, SVR 12+ weeks after end of treatment, patient satisfaction, and safety. Results: All 28 subjects (age 59 ± 7 years [mean ± SD], 61% male, 39% Caucasian, 93% treatment-naïve) had HCV genotype 1; 27 completed treatment. Most (82%) had <$25, 000 income/year, 46% had psychiatric comorbidities, and 32% had a history of drug abuse. The DMP was used for 92% of expected days; mean ingestion adherence was 94%. Providers used the DMP data for same-day adherence interventions in 39% of patients. SVR was achieved in 26 of 28 subjects (2 had failed prior therapy). One subject who did not achieve SVR had high adherence (≥95%), suggesting viral resistance; the other was non-adherent (<90%). Most (92%) agreed the DMP helped them feel more involved in managing their healthcare and easy to use in their daily routine; 85% agreed the DMP helped them understand the importance of taking medications regularly. Four subjects reported four nonserious adverse events of rash/pruritus, which resolved and were consistent with use of adhesives. Conclusion: These data suggest that the DMP may be used to support adherence to therapy through targeted, same-day adherence interventions, and optimize SVR rates, including in those with risk factors for nonadherence and in those who previously failed treatment. Disclosures: M. Bonacini, Proteus Digital Health: Investigator, Research support. Y. Kim, Proteus Digital Health: Consultant and Employee, Consulting fee and Salary. C. Pitney, Proteus Digital Health: Research Contractor, Research support. L. McKoin, Proteus Digital Health: Research Contractor, Research support. M. Tran, Proteus Digital Health: Employee, Salary. C. Landis, Proteus Digital Health: Investigator, Research support.